Report on the magnetic survey in Slovakia for the 2014.5 epoch - Fridrich VALACH; Magdaléna VÁCZYOVÁ; Tomáš ŠOLTIS; Melinda VAJKAI (Contributions to Geophysics and Geodesy, 2016)
The models of the distribution of the elements of the geomagnetic field must be updated regularly. For this purpose geomagnetic measurements have to be carried out repeatedly at geomagnetic observatories as well as at temporary observation points. In this paper the results of the geomagnetic survey that was carried out in Slovakia in the year 2014 are presented. The measurements were performed at 12 observation points and they were reduced to the 2014.5 epoch. The secular variation between 2007.5 and 2014.5 was also calculated. The obtained values of the geomagnetic elements were used for calculating a 1st-degree polynomial model for the distribution of magnetic declination, inclination and total field. The comparison with the IGRF model showed that the polynomial model provided more accurate results for magnetic inclination and total field. For magnetic declination, on the contrary, the IGRF model produced slightly better results than the polynomial model.